Lived experiences of families of meningitis patients and survivors in the Upper West Region of Ghana. - Damien Punguyire; Ambrose Naawa; Linus Baatiema; Simon Aabalekuu; Munawar Harun Koray; Avevor Patrick Mawupemor; Sally-Ann Ohene (PLOS Global Public Health)
Meningitis is a fatal condition and survivors often face long-term effects and often burdened their families. It is therefore important to understand how families cope with the aftermath of the infection. This study examined the experiences of families of meningitis patients and survivors in Ghana's Upper West Region to support public health interventions. The researchers employed a Giorgi phenomenological qualitative method to conduct the study between March and April 2023. Data were collected from 40 facilities and four District Health Directorates. Sixteen participants, including survivors and parents, were selected from meningitis linelists. The study employed content analysis, with a coding system revealing five main themes. Inter-coder reliability was checked, and peer debriefing was used to ensure credibility. The study identified five main challenges: reduced productivity, inability to perform labor-intensive work, financial strain on households, psychological trauma, and the impact of social support. These experiences highlight the subjective nature of post-meningitis challenges and are consistent with existing literature. Meningitis survivors and their families face physical, emotional, and financial challenges, which can have long-term impacts. However, social support plays a crucial role in resilience and recovery. The study recommends that health institutions establish follow-up programs to monitor long-term effects on survivors.